Genetic Variability in Half - Sib Seedlings of Term1nalia arjuna Bedd - Srivastava, P. K.; Siddiqui, A. A.; Goel, A. K. (Indian Forester, 1993)
Half sib seedlings belonging to 24 Terminalia arjunatrees located in M. P., Orissa and Bihar were quantitatively measured for leaf and height characters to assess variability and superiority in the seedlings. High heritability, high genetic advance and high genetic coefficient of variation were found for seedling height which indicates additive gene action for this character where as low GCV, low genetic advance and high heritability were noted for remaining leaf characters suggesting thereby intra and inter-allelic interaction for leaf characters. The O1, 02 and N4 have been found to be best performers in the descending order followed by D, Ds1, Nl, Ds4, N3, B1 and B2.